Formation of seed profitability in collective samples of soybean in the conditions of Ukraine’s Forest-Steppe - Білявська, Л. Г.; Рибальченко, А. М. (Scientific Progress & Innovations, 2018)
The article presents the results of research on the formation of seed productivity of soybean collection samples for 2013–2015. Evaluation of breeding material in a complex of economic and valuable features is important for the creation of new high-yield varieties with adaptive potential. The valuable samples for further breeding work have been selected for such important features as the mass of 1000 seeds and the amount of seed from the plant and the mass of seed from the plant, respectively. It was found that among the specimens of the ultra-fast-growing group on the basis of the mass of 1000 seeds, the samples such as OAS Vision (167.33 g), LF-8 (155.00 g), Gaillard (162.33 g), Zlata ( 150.00 g). In the fast-growing group, such varieties as Diamond (183.67 g), Ustia (179.33 g), Kivin (184.67 g), Adamos (164.67 g), Vlishanka (165.00 g), Mriya (168.00 g), South-40 (165.67 g), Fortun (168.00 g), Poem (171.00 g), Hvylia (173.00 g), Artemis (165.00 g) were better than the variety-standart Vasyl’kivska. The best-in-class than standard Chernivtsi-8 in the middle-eastern group of maturity was Podolianka (178.33 g), Masha (176.67 g), Farwater (176.33 g), Slavia (176.00 g), Eldorado (179.33 g), Ivanka (175.33 g). The sample Diamond (bi=0,96) is steady with a coefficient of regression (bi) with a high weight of 1000 seeds. One of the main signs in the structure of the plant, which determines the productivity of the variety, is the mass of seeds from the plant. On average, over three years in the ultra-fast-growing group, the collection samples formed a mass of seed from the plant – OAS Vision – 24.20 g, LF-8 – 22.33 g, Gaillard – 18.27 g, Zlata – 17.63 g. In the strain – Diamond 29.77 g, Ustia – 24.50 g, Kivin – 28.90 g, Adamos – 25.20 g, Vlishanka – 23.03 g, Dream – 24.63 g, South-40 – 23.60 g, Fortune – 23.40 g, Poem – 24,53 g, Hvylia – 28,57 g, Artemis – 22,37 g. In the middle-eastern group of ripeness – Podolianka – 27.83 g, Masha – 27.90 g, Farwater – 30.33 g, Slavia – 24.33 g, Eldorado – 28.83 g, Ivanka – 25.87 g. Regular bias stable (bi) with high weight of seed from the plant you Distributed Kivin samples (bi=0.87), OAC Vision (bi=0.35), LF-8 (bi=0.69). The average number of seeds from the plant in the collection varieties of soybeans varied in 2013 from 58.1 to 182.4 pcs., in 2014 – from 68.5 to 175.6 pp., in 2015 – from 54.6 to 173,1 pcs. On average over three years in the ultra-fast-growing group, the collection samples formed the amount of seed from the plant – OAS Vision – 127.30 pcs., LF-8 – 115.00 pcs., Gaillard – 111.80 pcs., Zlata – 104.63 pcs. In the fast-cutting – Diamond 136.37 units, Ustia – 121.77 units, Kivin – 177.03 units, Adamos – 125.67 units, Vil’shanka – 118.87 units, Mriya – 118.17 units, South-40 – 111.70 pieces, Fortuna – 119.03 units, Poem – 114.37 units, Hvylia – 141.90 units, Artemis – 111.73 units. In the middle age group of ripeness – Podolianka – 122.93 units, Masha – 125.77 units, Farwater – 131.07 units, Slavia – 120.10 units, Eldorado – 128.53 units, Ivanka – 119.67 pcs. A sample of Kivin (bi=0,97) is steady under the coefficient of regression (bi) with high amount of plant seeds. As a result of the research conducted on such important features as the mass of 1000 seeds, the amount of seed from the plant, the weight of the seeds from the plant highlighted valuable samples OAS Vision, LF-8, Gaillard, Zlata, Diamond, Ustia, Kivin, Adamos, Vil’shanka, Mriya, South-40, Fortune, Poem, Hvylia, Podolianka, Masha, Farwater, Slavia, Eldorado, Ivanka, which are expedient to use for further breeding work.